“FUN AND EFFECTIVE: TEACHING ENGLISH THROUGH GAMES” (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article highlights the advantages of incorporating games into the classroom, including how they can boost motivation, retention, and student involvement. It also includes studies on how game-based learning might enhance language proficiency and acquisition. For teachers looking to build engaging and dynamic learning environments for their students, this article is a valuable resource since it offers examples and concrete ideas for integrating games into English language training.